59.9k views
0 votes
Help ASAP show work please thanksss!!!!

Help ASAP show work please thanksss!!!!-example-1
User CMash
by
5.1k points

1 Answer

1 vote

Answer:


\displaystyle log_(1)/(2)(64)=-6

Explanation:

Properties of Logarithms

We'll recall below the basic properties of logarithms:


log_b(1) = 0

Logarithm of the base:


log_b(b) = 1

Product rule:


log_b(xy) = log_b(x) + log_b(y)

Division rule:


\displaystyle log_b((x)/(y)) = log_b(x) - log_b(y)

Power rule:


log_b(x^n) = n\cdot log_b(x)

Change of base:


\displaystyle log_b(x) = ( log_a(x))/(log_a(b))

Simplifying logarithms often requires the application of one or more of the above properties.

Simplify


\displaystyle log_(1)/(2)(64)

Factoring
64=2^6.


\displaystyle log_(1)/(2)(64)=\displaystyle log_(1)/(2)(2^6)

Applying the power rule:


\displaystyle log_(1)/(2)(64)=6\cdot log_(1)/(2)(2)

Since


\displaystyle 2=(1/2)^(-1)


\displaystyle log_(1)/(2)(64)=6\cdot log_(1)/(2)((1/2)^(-1))

Applying the power rule:


\displaystyle log_(1)/(2)(64)=-6\cdot log_(1)/(2)((1)/(2))

Applying the logarithm of the base:


\mathbf{\displaystyle log_(1)/(2)(64)=-6}

User Tomislav Novoselec
by
5.5k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.